2021
DOI: 10.1038/s41467-021-25362-4
|View full text |Cite
|
Sign up to set email alerts
|

A host–guest semibiological photosynthesis system coupling artificial and natural enzymes for solar alcohol splitting

Abstract: Development of a versatile, sustainable and efficient photosynthesis system that integrates intricate catalytic networks and energy modules at the same location is of considerable future value to energy transformation. In the present study, we develop a coenzyme-mediated supramolecular host-guest semibiological system that combines artificial and enzymatic catalysis for photocatalytic hydrogen evolution from alcohol dehydrogenation. This approach involves modification of the microenvironment of a dithiolene-em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 67 publications
(91 reference statements)
1
14
0
Order By: Relevance
“…Theoretical docking calculations suggested that the artificial host Pd– ZPP (Fe) possessed a well-matched opening for the inclusion of guest to form host – guest species Pd– ZPP (Fe) ⊃ RFT ( Figure 2 e, f). 18 The aromatic plane of RFT fell within the host cavity, and the aromatic plane was held snugly with the conjugate plane of porphyrin units by efficient aromatic stacking interactions (ca. 3.30 Å), whilst widespread hydrogen-bonding sites on Pd– ZPP (Fe) played an auxiliary role in trapping RFT, forming a sandwich supramolecular structure with a calculated Δ G of −35.03 kJ·mol – 1 ( Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretical docking calculations suggested that the artificial host Pd– ZPP (Fe) possessed a well-matched opening for the inclusion of guest to form host – guest species Pd– ZPP (Fe) ⊃ RFT ( Figure 2 e, f). 18 The aromatic plane of RFT fell within the host cavity, and the aromatic plane was held snugly with the conjugate plane of porphyrin units by efficient aromatic stacking interactions (ca. 3.30 Å), whilst widespread hydrogen-bonding sites on Pd– ZPP (Fe) played an auxiliary role in trapping RFT, forming a sandwich supramolecular structure with a calculated Δ G of −35.03 kJ·mol – 1 ( Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
“… 11 , 12 We envisioned that the incorporation of cofactor NADH and its mimics 13 , 14 into the surface of a catalyst-functionalized heteroleptic assembly would be an ideal toolkit to combine multiple individual active sites into catalytic pockets of enzymes, 15 , 16 enabling biological cascades by merging abiotic catalysis with cofactor-dependent enzymatic reactions in one working module. 17 , 18 Complementary to biological engineering, such approaches struggle to provide general solutions across gene expression limitation 19 and allow orthogonal cascades by compartmentalization, 20 making organic syntheses economically and ecologically worth undertaking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission. 189 Copyright 2021, Springer Nature. (D) A genetically encoded photosensitizer protein facilitates the rational design of a miniature photocatalytic CO 2 -reducing enzyme: schematic diagram of the proposed catalytic mechanism of the hybrid enzyme based on a geneticallyencoded photosensitizer protein (D1) and TON for CO formation, catalyzed by various PSP2 single-cysteine mutants (D2).…”
Section: Platform-based Aps'smentioning
confidence: 99%
“…Very recently, via the host–guest approach, Duan and coworkers reported a coenzyme-mediated semi-biological APS for hydrogen evolution from alcohol dehydrogenation. 189 As shown in Fig. 11C, the coenzyme photoregeneration system was fabricated by trapping a photosensitizer dye and NADH molecule into a metal–organic cage.…”
Section: Fabrication Of Apsmentioning
confidence: 99%